Essentials of Neurosurgical Anesthesia & Critical Care Strategies for Prevention, Early Detection, and Successful Management of Perioperative Complications - Brambrink, Ansgar M.; Kirsch, Jeffrey R. (Springer New York : Imprint: Springer, 2012)
This handbook is aimed at first-line health care providers involved in the perioperative care of adult and pediatric neurosurgical patients. It is unique in its systematic focus on how to deal with common and important clinical challenges encountered in day-to-day practice in the OR, the PACU, and the ICU and is designed as a problem-solving tool for all members of the perioperative medicine team: trainees and faculty in anesthesiology, neurosurgery, and critical care; nurses; nurse anesthetists; and physician's assistants.   • Encompasses clinical continuum from neurosurgical pre-op to critical care - plus anesthesia in neuroradiology • Adult and pediatric care • Structured algorithmic approach supports clinical decision-making • Succinct presentation of clinically relevant basic science • End-of-chapter summaries, with suggestions for further reading • Collaborative approach and multidisciplinary nature of perioperative medicine emphasized • Extensive summary tables • Portable and formatted for quick retrieval of information • Ideal for use in the OR, the PACU, and the ICU.